Gating and Regulation of KCNQ1 and KCNQ1 + KCNE1 Channel Complexes - Wang, Yundi; Eldstrom, Jodene; Fedida, David (Frontiers in Physiology, 2020)
The IKs channel complex is formed by the co-assembly of Kv7.1 (KCNQ1), a voltage-gated potassium channel, with its β-subunit, KCNE1 and the association of numerous accessory regulatory molecules such as PIP2, calmodulin, and yotiao. As a result, the IKs potassium current shows kinetic and regulatory flexibility, which not only allows IKs to fulfill physiological roles as disparate as cardiac repolarization and the maintenance of endolymph K+ homeostasis, but also to cause significant disease when it malfunctions. Here we review new areas of understanding in the assembly, kinetics of activation and inactivation, voltage-sensor pore coupling, unitary events and regulation of this important ion channel complex, all of which have been given further impetus by the recent solution of cryo-EM structural representations of KCNQ1 alone and KCNQ1+KCNE3. Recently, the stoichiometric ratio of KCNE1 to KCNQ1 subunits has been confirmed to be variable up to a ratio of 4:4, rather than fixed at 2:4, and we will review the results and new methodologies that support this conclusion. Significant advances have been made in understanding differences between KCNQ1 and IKs gating using voltage clamp fluorimetry and mutational analysis to illuminate voltage sensor activation and inactivation, and the relationship between voltage sensor translation and pore domain opening. We now understand that the KCNQ1 pore can open with different permeabilities and conductance when the voltage sensor is in partially or fully activated positions, and the ability to make robust single channel recordings from IKs channels has also revealed the complicated pore subconductance architecture during these opening steps, during inactivation, and regulation by 1-4 associated KCNE1 subunits. Experiments placing mutations into individual voltage sensors to drastically change voltage dependence or prevent their movement altogether have demonstrated that the activation of KCNQ1 alone and IKs can best be explained using allosteric models of channel gating. Finally, we discuss how the intrinsic gating properties of KCNQ1 and IKs are highly modulated through the impact of intracellular signalling molecules and co-factors such as PIP2, protein kinase A, calmodulin and ATP, all of which modulate IKs current kinetics and contribute to diverse IKs channel complex function.